Early medieval cemetery in Brzeg Głogowski district Głogów - Piontek, Janusz (Anthropological Review, 1974)
This paper contains the results of anthropological investigations of skeletons excavated on Xth — XIth c. A. D. cemetery from Lower Silesia. Archaeological dating have been made on ground of the such findings as: iron knives, clay pot, necklace and ring temple pendants. Investgated area covered about a half of the cemetery. On the ground of total number of graves, and duration of the cemetery mean number of persons in living group, which used this burial ground, was estimated to be about 30 - 40 individuals. 58 graves was excavated, in 35 of them estimation of sex and age was possible. In 8 graves (14.5%) were buried children died in age Inf. I, in 2 (3.6%) in age Inf. II and in 3 (5.6%) individuals died as juvenis. From total number (42) graves of adult individuals in 15 were buried women, in 23 men. In age Adultus died 40% of females and 43.5% of males, in age Maturus 60% and 52%, in age Senilis 0% and 4,4% respectively. The stature estimated with the use of Breitinger's formula is for males 168.2 cm (N = 20), and with the use of Bach's formula for females 161.8 cm (N = 5). Inter- and intrapopulation differentiation was investigated with the aid of Penrose's method and also was estimated anthropological composition according to Wanke's method. Typological analysis has shown high percentage values for mediterranean and nordic elements (e = 31.0%, a= 30.0%) and lower for laponoid and armenoid elements (I = 14.0%, h == 15.0%). In Penrose's method 10 skull characters were compared their mean valnes were divided by standard deviations for Ostrów Lednicki population. Distances C2G, CH and C2R were computed between investigated population and populations taken for comparison (see tab. 9). Population from Brzeg Glogowski is much more similar to populations from Wolin and Lower Silesia, its similarity to populations Irom Wielkopolska has a lesser degree. values of Penrose distances suggest a little differentiation of investigated characters on the whole area of origin of compared populations, so this populations have very similar morphological composition. In some instances the results obtained from comparisons of anlhropologleal cumpusilivus are in contrast to the values of Penrose distances (especially for Wolin and Ostrôw i Lednicki populations). Penrose's method let us show the real similarity in morphological traits of investigated population and comparative ones. Obtained results suggest that peoples buried on investigated cemetery have belonged to the Western Slaves population.